Evaluasi Proses Bisnis Menggunakan Quality Evaluation Framework (QEF) (Studi Kasus : UD Honda II Kepanjen AHASS 06641) - Intan Rumaysha; Aditya Rachmadi; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
The process of motorcycle maintenance is the main business process at UD Honda II Kepanjen Ahass 06641. In the process of motorcycle maintenance there are several activities performed, starting from customers come to perform maintenance, motorcycle maintenance work, until the motorcycle maintenance is done . In doing motorcycle maintenance activities occur some activities that are not in accordance with the target company, so it can hamper the existing activities in the company. Therefore, it is necessary to evaluate using Quality Evaluation Framework (QEF) method to know the gap that occurs between the target company with the results of calculations performed in QEF method. The first step is to identify the main business processes in the workshop, then model the business processes using Business Process Model and Notation (BPMN). Next determine the quality factor and target company, then performed calculations in accordance with the equations that is in the QEF method. Then identify the quality factor that is not in accordance with the target company. After finding the gap in the evaluation process, the next step is to do Root Cause Analysis, the purpose is to find the cause and root of the problem of the gap. The result of this research are the causes and effects that occur in the activity or process that has been evaluated.